ANALISIS KEKUATAN DAN STABILITAS STRUKTUR SISTEM PARKIR OTOMATIS BERBANTUAN SOFTWARE - Eko Reinaldo; Agustinus Purna Irawan; Frans Jusuf Daywin (Program Studi Teknik Mesin Universitas Tarumanagara, 2017)
Abstract: structure analysis software. Resulted of Automatic parking system is a car parking system which moves the vehicle from the parking lot entrance to the parking space automatically with no drivers. Automatic car parking system accepts the load's structure which should be done by the calculation and the structural strength analysis to get a strong and stable structure with expected safety level. structural strength analysis which has been done in this thesis is strong and stable automatic car parking system structure design.The analysis in this thesis is undertaken by using of structure analysis software. Resulted of structural strength analysis which has been done in this thesis is strong and stable automatic car parking system structure design